Effects of short-term experimental manipulation of captive social environment on uropygial gland microbiome and preen oil volatile composition - Whittaker, Danielle J.; Atyam, Amruth; Burroughs, Nathan A.; Greenberg, Jonathan M.; Hagey, Travis J.; Novotny, Milos V.; Soini, Helena A.; Theis, Kevin R.; Van Laar, Tricia A.; Slade, Joel W. G. (Frontiers in Ecology and Evolution, 2023)
Avian preen oil, secreted by the uropygial gland, is an important source of volatile compounds that convey information about the sender's identity and quality, making preen oil useful for the recognition and assessment of potential mates and rivals. Although intrinsic factors such as hormone levels, genetic background, and diet can affect preen oil volatile compound composition, many of these compounds are not the products of the animal's own metabolic processes, but rather those of odor-producing symbiotic microbes. Social behavior affects the composition of uropygial microbial communities, as physical contact results in microbe sharing. We experimentally manipulated social interactions in captive dark-eyed juncos (Junco hyemalis) to assess the relative influence of social interactions, subspecies, and sex on uropygial gland microbial composition and the resulting preen oil odor profiles. We captured 24 birds at Mountain Lake Biological Station in Virginia, USA, including birds from two seasonally sympatric subspecies – one resident, one migratory. We housed them in an outdoor aviary in three phases of social configurations: first in same-sex, same-subspecies flocks, then in male-female pairs, and finally in the original flocks. Using samples taken every four days of the experiment, we characterized their uropygial gland microbiome through 16s rRNA gene sequencing and their preen oil volatile compounds via GC-MS. We predicted that if social environment was the primary driver of uropygial gland microbiome composition, and if microbiome composition in turn affected preen oil volatile profiles, then birds housed together would become more similar over time. Our results did not support this hypothesis, instead showing that sex and subspecies were stronger predictors of microbiome composition. We observed changes in volatile compounds after the birds had been housed in pairs, which disappeared after they were moved back into flocks, suggesting that hormonal changes related to breeding condition were the most important factor in these patterns. Although early life social environment of nestlings and long-term social relationships have been shown to be important in shaping uropygial gland microbial communities, our study suggests that shorter-term changes in social environment do not have a strong effect on uropygial microbiomes and the resulting preen oil volatile compounds.